Design and analysis of orbital pipe welding prototype for piping system welding applications - Agus Widyianto; Ario Sunar Baskoro; Gandjar Kiswanto (Universitas Negeri Yogyakarta, 2024)
Welding the joints of pipes is often required for maintenance and repairs in industrial applications, where pipes are frequently used. A prototype of an orbital pipe welding machine was constructed, and its design, analysis, and construction were carried out. The goal of this endeavor was to improve the quality of the welding process as well as overall productivity. The design study was carried out with the assistance of the SolidWorks program, which allowed for the determination of the stress, strain, displacement, and factor of safety imposed on the gear section throughout the welding and pipe installation process. During pipe installation, the gear section experiences maximum stresses of 3.920e+12 MPa, 5.029e+05 MPa, and 2.239e+06 MPa, respectively. These stresses are a result of the pipe being installed. When the pipe is installed, the highest strain in the gear section is 1.802e+01%, 3.030e-06%, and 8.439e-06%, respectively. This strain happens when the pipe is installed. In addition, the maximum displacement in the gear section is 3.074e+09 mm, 3.215e+04 mm, and 6.312e-03 mm, respectively, when the pipe is mounted and the pipe is installed. With a value of 1.5, the analysis results demonstrated that the maximum stresses, strains, and displacements in the gear section during the welding process are sufficient to fulfill the requirements for the critical safety factor. This demonstrates that the orbital pipe welding equipment may be utilized to generate welds of superior quality while simultaneously enhancing both productivity and efficiency through its utilization.